The Emotional Costs of Solidarity: How Refugees and Volunteers Manage Emotions in the Integration Process - Spit, Neeltje (2025)
While emerging right‐wing populist voices are calling to prevent the arrival of refugees and their integration, volunteers perform solidarity by performing activities to support refugee integration. Most studies on these forms of solidarity in diversity focus on the quality and effectiveness of the activities. The emotional labor involved has received limited attention. To consider this emotional labor in more detail, we use Arlie Hochschild’s concept of feeling and framing rules and relate these rules to prevailing citizenship regimes, distinguishing between the self‐reliance regime and the community regime. Based on in‐depth ethnographic research of volunteer solidarity work in a deprived urban neighborhood and a middle‐class commuter town in the Netherlands, we show that volunteers are strongly aligned with the community regime, which involves navigating a multitude of feeling rules they struggle with. Refugees are more aligned with the self‐reliance regime, which also gives way to emotional struggles. We argue that to promote solidarity in diversity, scholars and policymakers should pay more attention to these different forms of emotional labor and the painful and joyful emotions involved.